Some Issues of the Development of Teachers' Adaptive Competence - Sayyora Toraeva (Universitas Muhammadiyah Sidoarjo, 2022)
The article discusses the issue of flexibility competence of teachers in the process of continuing education. Today, when school education and the role of the teacher are being renewed, teachers are required not only to teach in the classroom, but also to meet the special needs of students. Therefore, teachers today need to have competencies such as flexibility, including a evidence-based approach that allows them to adapt their activities to the new needs of students